Ma Xing Shi Gan Decoction Attenuates PM2.5 Induced Lung Injury via Inhibiting HMGB1/TLR4/NFκB Signal Pathway in Rat - Fei, Yu-xiang; Zhao, Bo; Yin, Qi-yang; Qiu, Yan-ying; Ren, Guang-hui; Wang, Bo-wen; Wang, Ye-fang; Fang, Wei-rong; Li, Yun-man (Frontiers in Pharmacology, 2019)
Ma Xing Shi Gan Decoction (MXD), a classical traditional Chinese medicine prescription, is widely used for the treatment of upper respiratory tract infection. However, the effect of MXD against particulate matters with diameter of less than 2.5 μm (PM2.5) induced lung injury remains to be elucidated. In this study, rats were stimulated with PM2.5 to induce lung injury. MXD was given orally once daily for five days. Lung tissues were harvested to assess pathological changes and edema. Myeloperoxidase (MPO) activity and malonaldehyde (MDA) content in lung were determined to evaluate the degree of injury. To assess the barrier disruption, the bronchoalveolar lavage fluid (BALF) was collected to determine the total protein content and count the number of neutrophils and macrophages. For evaluating the activation of macrophage in lung tissue, CD68 was detected using immunohistochemistry (IHC). The levels of inflammatory factors including tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β) and interleukin-6 (IL-6) in BALF and serum were measured. In vitro, a PM2.5-activated RAW 264.7 macrophages inflammatory model was introduced. To evaluate the protective effect of MXD-medicated serum, the cell viability and the release of inflammatory factors were measured. The effects of MXD on the High mobility group box-1/Toll-like receptor 4/Nuclear factor-kappa B (HMGB1/TLR4/NFκB) pathway in lung tissue and RAW 264.7 cells were assessed by Western blot. For further confirming the protective effect of MXD was mediated by inhibiting the HMGB1/TLR4/NFκB pathway, RAW 264.7 cells were incubated with MXD-medicated serum alone or MXD-medicated serum plus recombinant HMGB1 (rHMGB1). MXD significantly ameliorated the lung injury in rats, as evidenced by decreases in the pathological score, lung edema, MPO activity, MDA content, CD68 positive macrophages number, disruption of alveolar capillary barrier and the levels of inflammatory factors. In vitro, MXD-medicated serum increased cell viability and inhibited the release of inflammatory cytokines. Furthermore, MXD treatment was found to inhibit HMGB1/TLR4/NFκB signal pathway both in vivo and in vitro. Moreover, the protection of MXD could be reversed by rHMGB1 in RAW 264.7. Taken together, these results suggest MXD protects rats from PM2.5 induced acute lung injury, possibly through the modulation of HMGB1/TLR4/NFκB pathway and inflammatory responses.